Variable wind, pack ice, and prey dispersion affect the long‐term adequacy of protected areas for an Arctic sea duck. Issue 2 (1st March 2014) - Lovvorn, James R.; Anderson, Eric M.; Rocha, Aariel R.; Larned, William W.; Grebmeier, Jacqueline M.; Cooper, Lee W.; Kolts, Jason M.; North, Christopher A.
Abstract : With changing climate, delineation of protected areas for sensitive species must account for long‐term variability and geographic shifts of key habitat elements. Projecting the future adequacy of protected areas requires knowing major factors that drive such changes, and how readily the animals adjust to altered resources. In the Arctic, the viability of habitats for marine birds and mammals often depends on sea ice to dissipate storm waves and provide platforms for resting. However, some wind conditions (including weak winds during extreme cold) can consolidate pack ice into cover so dense that air‐breathing divers are excluded from the better feeding areas. Spectacled Eiders ( Somateria fischeri ) winter among leads (openings) in pack ice in areas where densities of their bivalve prey are quite high. During winter 2009, however, prevailing winds created a large region of continuous ice with inadequate leads to allow access to areas of dense preferred prey. Stable isotope and fatty acid biomarkers indicated that, under these conditions, the eiders did not diversify their diet to include abundant non‐bivalve taxa but did add a smaller, less preferred, bivalve species. Consistent with a computer model of eider energy balance, the body fat of adult eiders in 2009 was 33–35% lower than on the same date (19 March) in 2001 when ice conditions allowed access to higher bivalve densities. Ice cover data suggest that the eiders were mostly excluded from areas of high bivalve density from January to March in about 30% of 14 winters from 1998 to 2011. Thus, even without change in total extent of ice, shifts in prevailing winds can alter the areal density of ice to reduce access to important habitats. Because changes in wind‐driven currents can also rearrange the dispersion of prey, the potential for altered wind patterns should be an important concern in projecting effects of climate change on the adequacy of marine protected areas for diving endotherms in the Arctic.